Corrigendum to ’changing Pseudo-nitzschia and Dinophysis distributions in the North Sea and Western approaches (NE Atlantic) and their potential use in biodiversity assessments’ [harmful algae 156 (2026) 103113] - Matthew M. Holland; Eileen Bresnan; Martin Edwards; Matthew Faith; Clare Ostle; Rowena Stern; Paul Tett; Claire Widdicombe; Callum Whyte; Abigail McQuatters-Gollop (Harmful Algae, 2026)

Changing Pseudo-nitzschia and Dinophysis distributions in the North Sea and Western Approaches (NE Atlantic) and their potential use in biodiversity assessments - Matthew M Holland; Eileen Bresnan; Martin Edwards; Matthew Faith; Clare Ostle; Rowena Stern; Paul Tett; Claire Widdicombe; Callum Whyte; Abigail McQuatters-Gollop (Harmful Algae, 2026)

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

Operational modelling to assess advective harmful algal bloom development and its potential to impact aquaculture - Paul Dees; Andrew Dale; Callum Whyte; Beth Mouat; Keith Davidson (Harmful Algae, 2023)

Novel Methodologies for Providing In Situ Data to HAB Early Warning Systems in the European Atlantic Area: The PRIMROSE Experience - Manuel Ruiz-Villarreal; Marc Sourisseau; Phil Anderson; Caroline Cusack; Patricia Neira; Joe Silke; Francisco Rodriguez; Begoña Ben-Gigirey; Callum Whyte; Solene Giraudeau-Potel; Loic Quemener; Gregg Arthur; et al. (Frontiers in Marine Science, 2022)
Harmful algal blooms (HABs) cause harm to human health or hinder sustainable use of the marine environment in Blue Economy sectors. HABs are temporally and spatially variable and hence their mitigation is closely linked to effective early warning. The European Union (EU) Interreg Atlantic Area project “PRIMROSE”, Predicting Risk and Impact of Harmful Events on the Aquaculture Sector, was focused on the joint development of HAB early warning systems in different regions along the European Atlantic Area. Advancement of the existing HAB forecasting systems requires development of forecasting tools, improvements in data flow and processing, but also additional data inputs to assess the distribution of HAB species, especially in areas away from national monitoring stations, usually located near aquaculture sites. In this contribution, we review different novel technologies for acquiring HAB data and report on the experience gained in several novel local data collection exercises performed during the project. Demonstrations include the deployment of autonomous imaging flow cytometry (IFC) sensors near two aquaculture areas: a mooring in the Daoulas estuary in the Bay of Brest and pumping from a bay in the Shetland Islands to an inland IFC; and several drone deployments, both of Unmanned Aerial Vehicles (UAV) and of Autonomous Surface vehicles (ASVs). Additionally, we have reviewed sampling approaches potentially relevant for HAB early warning including protocols for opportunistic water sampling by coastguard agencies. Experiences in the determination of marine biotoxins in non-traditional vectors and how they could complement standard routine HAB monitoring are also considered.

Current Status of Forecasting Toxic Harmful Algae for the North-East Atlantic Shellfish Aquaculture Industry - Jose A. Fernandes-Salvador; Keith Davidson; Marc Sourisseau; Marta Revilla; Wiebke Schmidt; Dave Clarke; Peter I. Miller; Paola Arce; Raúl Fernández; Luz Maman; Alexandra Silva; Callum Whyte; et al. (Frontiers in Marine Science, 2021)
Across the European Atlantic Arc (Scotland, Ireland, England, France, Spain, and Portugal) the shellfish aquaculture industry is dominated by the production of mussels, followed by oysters and clams. A range of spatially and temporally variable harmful algal bloom species (HABs) impact the industry through their production of biotoxins that accumulate and concentrate in shellfish flesh, which negatively impact the health of consumers through consumption. Regulatory monitoring of harmful cells in the water column and toxin concentrations within shellfish flesh are currently the main means of warning of elevated toxin events in bivalves, with harvesting being suspended when toxicity is elevated above EU regulatory limits. However, while such an approach is generally successful in safeguarding human health, it does not provide the early warning that is needed to support business planning and harvesting by the aquaculture industry. To address this issue, a proliferation of web portals have been developed to make monitoring data widely accessible. These systems are now transitioning from “nowcasts” to operational Early Warning Systems (EWS) to better mitigate against HAB-generated harmful effects. To achieve this, EWS are incorporating a range of environmental data parameters and developing varied forecasting approaches. For example, EWS are increasingly utilizing satellite data and the results of oceanographic modeling to identify and predict the behavior of HABs. Modeling demonstrates that some HABs can be advected significant distances before impacting aquaculture sites. Traffic light indices are being developed to provide users with an easily interpreted assessment of HAB and biotoxin risk, and expert interpretation of these multiple data streams is being used to assess risk into the future. Proof-of-concept EWS are being developed to combine model information with in situ data, in some cases using machine learning-based approaches. This article: (1) reviews HAB and biotoxin issues relevant to shellfish aquaculture in the European Atlantic Arc (Scotland, Ireland, England, France, Spain, and Portugal; (2) evaluates the current status of HAB events and EWS in the region; and (3) evaluates the potential of further improving these EWS though multi-disciplinary approaches combining heterogeneous sources of information.

HABreports: Online Early Warning of Harmful Algal and Biotoxin Risk for the Scottish Shellfish and Finfish Aquaculture Industries - Keith Davidson; Callum Whyte; Dmitry Aleynik; Andrew Dale; Steven Gontarek; Andrey A. Kurekin; Sharon McNeill; Peter I. Miller; Marie Porter; Rachel Saxon; Sarah Swan (Frontiers in Marine Science, 2021)
We present an on-line early warning system that is operational in Scottish coastal waters to minimize the risk to humans and aquaculture businesses in terms of the human health and economic impacts of harmful algal blooms (HABs) and their associated biotoxins. The system includes both map and time-series based visualization tools. A “traffic light” index approach is used to highlight locations at elevated HAB/biotoxin risk. High resolution mathematical modelling of cell advection, in combination with satellite remote sensing, provides early warning of HABs that advect from offshore waters to the coast. Expert interpretation of HAB, biotoxin and environmental data in light of recent and historical trends is used to provide, on a weekly basis, a forecast of the risk from HABs and their biotoxins to allow mitigation measures to be put in place by aquaculture businesses, should a HAB event be imminent.